Pengembangan Media Portofolio Elektronik Melalui Teknologi Self Video on Demand On-Line (Svodoo) Sebagai Penguatan Aspek Sosial dan Emosional Bagi Calon Guru Di Lingkungan LPTK - Sihkabuden; Arafah Husna; Henry Praherdhiono (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
Teacher candidates in the LPTK require special attention in their assessment methods. Primary responsibility for teacher change rests on the preparation program for prospective teachers in higher education (Lombardi and Hunka, 2001). Prospective teachers in the LPTK have a variety of complex dimensions. So it requires social and emotional learning content that is able to effectively acquire all the potential of prospective teachers in order to provide the knowledge, attitudes and skills needed to recognize and manage emotions, develop concern for others, make responsible decisions, build relationships, and handle academic situations. who have a positive attitude. The application of SVODO technology in learning and learning can be categorized as a simple and realistic media portfolio. Davidson and Rasmussen's (2007) Development Model was chosen based on its suitability to the characteristics of developing an On-line learning management system.